Does low frequency noise affect human mental performance? - Pawlaczyk-Łuszczyńska, M.; Dudarewicz, A.; Waszkowska, M.; Szymczak, W.; Kameduła, M.; Śliwińska-Kowalska, M. (Archives of Acoustics, 2004)
To study the influence of low frequency noise (LFN) on mental performance and subjective well-being, 192 male subjects, categorised in terms of sensitivity to noise in general, and to LFN in particular, worked with four standardised psychological tests. Three different acoustic conditions were used in the experiment: the background laboratory noise, LFN, and the broadband noise without dominant low frequency content (reference noise) at a level of 50 dB(A). The influence of exposure and/or noise sensitivity on the tests’ results or their interaction were found in three of the four performed tests. Poorer results in the LFN (compared to other noise conditions) were observed in person classified as high-sensitive to noise in general and low-sensitive to LFN in the Signal Detection Test (more erroneous responses). The annoyance of LFN and reference noise was rated higher than that of the background noise. Subjects high-sensitive to noise in general reported the highest annoyance due to LFN. In conclusion, LFN at moderate level could be perceived as annoying and adversely affecting attention and visual perception, particularly in subjects high-sensitive to noise.